COVID-19: the economic collapse in India - Rakhi Arora; Sonal Purohit; Shikha Agarwal (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2021)
COVID-19 has upended societies and dramatically altered everyday life across the globe. The outbreak of COVID-19 in different parts of the world is a major concern for all the administrative units of respective countries. India is also facing this very tough task of spreading virus. COVID-19 impacts have been outlined and clarified in depth in this study. It has been explored that how corona virus, originated in Wuhan, China has resulted in economic collapse in India affecting the individual lives and business firms, in fact every sector of the country, due to which economic growth of every country in the world is hampered. This has been explained by reviewing the facts and information taken from secondary sources. The responsible factors for economic disruption have also been stated in this study with the economic outlook of Indian economy.